Pengaruh Pertumbuhan Penjualan, Pertumbuhan Laba dan Intellectual Capital Terhadap Harga Saham - Haryono, Mia Agustina; Indawati (Disclosure: Journal of Accounting and Finance, 2024)
Thi study aims to examine and analyze the influence of Sales Growth, Profit Growth, and Intellectual Capital on Stock Prices of consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020. This type of research is quantitative, utilizing secondary data. The data analysis method used is panel data regression analysis with the help of Microsoft Excel and E-views 12. The population in this study comprises all consumer non-cyclical sectors listed on the IDX for the period 2018 to 2022. The data collection technique in this study is purposive sampling, resulting in 35 samples from a population of 112, which were processed in this study. The results indicate that Sales Growth, Profit Growth, and Intellectual Capital simultaneously influence stock prices of consumer non-cyclical companies for the period 2018 to 2022. However, partially, Sales Growth does not affect Stock Prices, Profit Growth does not affect Stock Prices, while Intellectual Capital does affect Stock Prices.